Surface layer scintillometry for estimating the sensible heat flux component of the surface energy balance - G. Odhiambo; M. Savage (South African Journal of Science)
The relatively recently developed scintillometry method, with a focus on the dual-beam surface layer scintillometer (SLS), allows boundary layer atmospheric turbulence, surface sensible heat and momentum flux to be estimated in real-time. Much of the previous research using the scintillometer method has involved the large aperture scintillometer method, with only a few studies using the SLS method. The SLS method has been mainly used by agrometeorologists, hydrologists and micrometeorologists for atmospheric stability and surface energy balance studies to obtain estimates of sensible heat from which evaporation estimates representing areas of one hectare or larger are possible. Other applications include the use of the SLS method in obtaining crucial input parameters for atmospheric dispersion and turbulence models. The SLS method relies upon optical scintillation of a horizontal laser beam between transmitter and receiver for a separation distance typically between 50 and 250 m caused by refractive index inhomogeneities in the atmosphere that arise from turbulence fluctuations in air temperature and to a much lesser extent the fluctuations in water vapour pressure. Measurements of SLS beam transmission allow turbulence of the atmosphere to be determined, from which sub-hourly, real-time and in situ path-weighted fluxes of sensible heat and momentum may be calculated by application of the Monin-Obukhov similarity theory. Unlike the eddy covariance (EC) method for which corrections for flow distortion and coordinate rotation are applied, no corrections to the SLS measurements, apart from a correction for water vapour pressure, are applied. Also, path-weighted SLS estimates over the propagation path are obtained. The SLS method also offers high temporal measurement resolution and usually greater spatial coverage compared to EC, Bowen ratio energy balance, surface renewal and other sensible heat measurement methods. Applying the shortened surface energy balance, measurements of net irradiance and soil heat as well as SLS estimates of sensible heat allows path-weighted evaporation from the surface to be estimated. Research applications involving the use of the SLS method, as well as the theory on which the method is based, are presented.